A coupled multibody - mid fidelity aerodynamic tool for the simulation of tiltrotor manoeuvres - Savino, A.; Cocco, A.; Zanoni, A.; Zanotti, A.; Muscarello, V. (My University, 2021)
A nonlinear aeroelastic numerical tool was used in the present work for the evaluation of loads and vibratory levels of a tiltrotor aircraft during critical transient manoeuvres. The numerical tool applicable to fixed and rotary-wing aircraft was obtained by joining the multibody solver MBDyn and the mid-fidelity aerodynamic tool DUST, through the partitioned Multiphysics coupling library preCICE. The aim of this work was to assess the ability of the nonlinear approach implemented in the coupled MBDyn-DUST tool for the simulation of tiltrotor aerodynamics and dynamics during a roll manoeuvre to be used for the preliminary design of novel tiltrotor configurations. This activity was performed in the framework of the EU funded CleanSky 2 FORMOSA project, aimed to the design of a novel wing movable surface system for the NextGen Civil Tiltrotor aircraft.